Main risks and importance of treatment related to ectopic pregnancy (Research, Society and Development, 2021)
This article aims to describe the main risks and the importance of treatment related to ectopic pregnancy. This is an integrative literature review, a study of knowledge synthesis based on the analysis of available evidence, in a systematic and rigorous way. The guiding question of this study was: What are the main risks and importance of treatment related to ectopic pregnancy? The research included: complete articles available free of charge, languages ​​in Portuguese, English and Spanish. Excluding duplicate, unavailable and incomplete articles, with a time frame from 2014 to 2021. The rescue of the studies occurred from the controlled descriptors DeCS (Descriptors in Health Sciences): "ectopic pregnancy", "treatment", "risks" and “care”. The databases consulted were: MEDLINE (Medical Literature Analysis and Retrieval System Online), LILACS (Latin American Caribbean Literature in Health Sciences), academic Google and the SciELO virtual library. From the data collection, 705 studies were found. The first phase of the analysis consisted of applying the inclusion and exclusion criteria. With that, 7 articles were obtained at the end of the first phase. In the second phase, the reading of the 6 studies was carried out to find those that correctly answered the research's guiding question and/or were adequate to the phenomenon of the study. Therefore, the relevance of the topic discussed is shown, as well as all its forms and presentations that involve from infertility to the death of many women, and studies continue showing the importance of early diagnosis, as well as less invasive treatments aiming at a lower impact in women's lives.